Hubungan antara kecerdasan emosional dan prestasi belajar dengan penggunaan social media pada siswa SMA - Mulawarman Mulawarman; Fahmi Nuzulul Huda; Suharso Suharso; Muslikah Muslikah (Jurnal Konseling dan Pendidikan, 2019)
This study aims to examine the correlation between emotional intelligence (EI) and learning achievement with social media usage on students. The kind of this research is correlation quantitative. Subjects were 4 of 10 schools with 226 students and using cluster random sampling and purposive sampling. The data were obtained by the questionnaire of social media usage, the scale of emotional intelligence (EI), and the ledger documentation. Validity rate on all of the instruments was high with the level of error 5%, as well as the reliability of the instruments which was also high. The descriptive analysis using the mean and standard deviation, while hypothesis testing using the product moment correlation and multiple. The research results prove negative and significant relationship between EI with social media usage (rxy = -0.251; p